1) (-3a^2bc)^3/18a^4b^5c^3

simplify completely. no negative exponents

Thank you for the opportunity to help you with your question!

(-3a^2bc)^3/18a^4b^5c^3

=-27a^6b^3c^3/18a^4b^5c^3

=(-3a^2)/(2b^2)

Why did you distrubuted the b^3 and c^3?? isn't it together so bc^3?

no, b and c are two different variable

its (bc)^3 =b^3 *c^3

for example,

(2*3)^2 =6^2 =36 and 2^2 *3^2 =36

if u want more better explanation than ask me more questions directly in paid mode and not prepaid .

I will give you thorough explanations.

Thanks.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up